2014
DOI: 10.1111/rssa.12062
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Income Inequality Measures on Human Immunodeficiency Virus Mortality: a Spatiotemporal Bayesian Perspective

Abstract: Summary Social, economic, environmental and behavioural factors impacting health are well recognized in the literature. We consider the use of various income inequality measures in addition to a poverty measure and investigate their effects on human immunodeficiency virus (HIV) mortality. In doing so, we make use of models that can capture zero inflation and spatiotemporal effects. The research is motivated by the lack of studies from an inference and modelling perspectives in explaining HIV mortality by using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Another possibility might be to consider a spatial structure to define the dependence across teeth, perhaps along the lines of some previous work. () Intuitively, we may expect that adjacent teeth are highly correlated and that the dependence decays farther away the teeth are located. In principle, our model can handle this approach by defining a γ i j and δ i j term for every tooth, and the full vector is drawn from MVN with covariance matrix Σ i that provides a (low‐dimension) spatial structure on the basis of tooth location.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possibility might be to consider a spatial structure to define the dependence across teeth, perhaps along the lines of some previous work. () Intuitively, we may expect that adjacent teeth are highly correlated and that the dependence decays farther away the teeth are located. In principle, our model can handle this approach by defining a γ i j and δ i j term for every tooth, and the full vector is drawn from MVN with covariance matrix Σ i that provides a (low‐dimension) spatial structure on the basis of tooth location.…”
Section: Discussionmentioning
confidence: 99%
“…() There are also mixed effects models for zero‐inflated clustered data that use random effects to introduce dependence. () However, these methods are typically limited to the equidispersed or overdispersed cases because of the properties of Poisson and negative binomial distributions.…”
Section: Introductionmentioning
confidence: 99%
“…There is also a clear connection between a person’s socioeconomic situation and his or her state of health [ 7 ]. Abundant professional literature and copious findings on this issue demonstrate a relation between income inequality and disparities and mortality and other health indicators [ 1 , 30 , 36 ]. A study encompassing data from twenty-two European countries, for example, found that in almost all countries surveyed, low-socioeconomic-status groups had higher mortality rates and lower health self-assessments than those of high socioeconomic status [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…The data exhibit a complex dependence structure. Counties are nested within states, and adjacent counties are considered to be geographically correlated (Aktekin and Musal, ; Musal and Aktekin, ). The observations from different counties within a state are likely to be impacted by state level policies; thus, they are possibly correlated.…”
Section: Introductionmentioning
confidence: 99%